IMPLEMENTASI PENGEMBANGAN ENTERPRENEURSHIP DALAM KURIKULUM PRODI PGMI INSTITUT PESANTREN MATHALI’UL FALAH PATI-JAWA TENGAH - Ulya, Inayatul (Pascasarjana IAIN Kudus, 2017)
One of the problems faced by countries emerging is the number of people living in poverty. Therefore, poverty reduction a priority in the implementation of economic development. For Indonesia, the reduction of poverty is one measure of the success of development. Considering the number of the world's population in poverty, it is natural for poverty become an international problem. It proved , the PBB has set Millennium Development Goals ( MDGs ), where one of the goal is to reduce poverty . as a high-level conference participants millenium of PBB, Indonesia seriously to reduce the number of poor people to reach 50 % by 2015. Poverty is a complex issue, so that countermeasures need approaches from various aspects, whether economic, political and socio-cultural. One of the solutions is through educational activities entrepreneurship in order to change the mental attitude of dependence and to develop a work ethic, which is expected to foster self-reliance. Through the implementation of entrepreneurship education is expected to raise the awareness that to eliminate poverty must be taken through the productive work carried out by their own. Then, Prodi PGMI of Institut Pesantren Mathali’ul Falah intends to develop entrepreneurship in the curriculum design and learning experiences so that graduates can survive in his life later